Cycling economy following a 3-wk natural altitude training camp (~2700) in nationally competitive cyclists - Martin, D. T.; Quod, M.; Garvican, L. A.; Etxebarria, N.; Stephens, B.; Impellizzeri, F. M.; Rampinini, E.; Sassi, A.; Gore, C. J. (Medicine & Science in Sports & Exercise, 2008)
The effects of altitude training on submaximal oxygen uptake (VO2) at sea level are equivocal. Improvements in economy are often reported by research groups using high precision VO2 measurements and 2-4wk research centered altitude camps. PURPOSE: To document the effects a 3-wk natural altitude training camp on submaximal VO2 in nationally competitive cyclists preparing for the World Championships. METHODS: 9 male cyclists (Mean±SD mass, age, VO2max: 68±6 kg , 21±1 y, 74±5 ml.kg-1.min-1) completed a submaximal cycle ergometer test at ~300-600m (5min @ 2, 3, 4 W.kg-1, ~90rpm). Testing was performed twice before and once following a 3-4wk training camp. 5 cyclists lived and slept at 2760m for 21 nights (ALT) while 4 cyclists lived and slept at ~600m for 28 nights (SL). Both groups completed a high volume, low intensity training program (~600-900km per wk) including frequent hill climbing (~10-15,000m climbing per wk). A breath-by-breath automated gas analysis system (VMAX29, Sensormedics) was used for ALT and an automated Douglas Bag System was used for SL. The last 2min of each 5min stage were averaged for analysis. Typical Error (TE) was calculated from duplicate measures performed prior to the training camp. Iron supplementation (305mg ferrous sulphate) was administered daily throughout the study for all cyclists. RESULTS: TE for each of the three submaximal work loads (2, 3, 4 W.kg-1) ranged from: .07-.09 L.min-1 VO2, .06-.08 L.min-1 VCO2, 1.5-4.2 L.min-1 VESTPD and .022-.028 RER. The %CV range for each 2min sample was ~2-10%. SL training did not noticeably influence submaximal VO2, VCO2, VESTPD or RER. However, ALT training was associated with a "likely" increase in VO2 (Mean±90%CI; .19±.11, .19±.13, .18±.22 L.min-1; p<.05), VCO2 (.24±.08, .22±.08, .23±.11 L.min-1; p<.01) and VESTPD (8±4, 9±2, 12±6 L.min-1; p<.01). RER after ALT was "unlikely" different from baseline values due to similar increases in VO2 and VCO2 post ALT. CONCLUSION: In contrast to previous live high train low research, an increase in submaximal VO2 (1-10%) occurred in all cyclists following altitude training. The increase in VO2 can almost fully be attributed to the 5-10% increase in VE. These changes in economy may be explained by the unique timing and training content of the altitude camp or methodological limitations associated with assessing VO2.